The study of oilseed flax varieties in the Kostroma region - S. A. Kruglova (Зерновое хозяйство России)
The current paper has presented the results of ecological and geographical testing of oilseed flax varieties in the Kostroma region. The purpose of the current study was to identify promising oilseed flax varieties adapted to the soil and climatic conditions of our region. The objects of the study were 5 varieties ‘Biryuza’, ‘Rucheek’, ‘Nilin’, ‘Fliz’ and ‘VNIIMK 620’ (as the standard variety) developed in the of the ‘FRC VNIIMK named after V.S. Pustovoit’. The trials were laid down, recorded and observed according to the methodology of a field trial, as well as in accordance with the recommendations for conducting field agrotechnical experiments with oilseeds. There has been established a reaction of varieties to the agrometeorological conditions of the region. The vegetation period of flax ranged from 103 to 110 days. There was revealed that these varieties of the middle-maturing group, showed themselves as late-maturing during the study. On average, over the years of study, the highest seed productivity was given by the varieties ‘Biryuza’ (1.16 t/ha) and ‘Fliz’ (1.12 t/ha). All varieties had a high positive correlation between seed productivity and plant density per m2 . The largest oil content was identified in the varieties ‘Biryuza’ (50.2%) and ‘Rucheek’ (50.3%). The largest oil productivity was given by the varieties ‘Biryuza’ (0.58 t/ha) and ‘Rucheek’ (0.56 t/ha). The largest seeds were formed by the varieties ‘VNIIMK 620’ (7.92 g) and ‘Fliz’ (8.34 g). There has been established that two varieties ‘Biryuza’ and ‘Rucheek’ are the best ones among the studied varieties according to the main economically valuable traits. In the soil and climatic conditions of the Kostroma region, there can be formed complete flax seeds with high varietal and sowing qualities despite the increase in their vegetation period length.